2011
DOI: 10.1002/jcu.20886
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative US‐guided hookwire localization for nonpalpable cervical masses

Abstract: Preoperative US-guided hookwire insertion in nonpalpable cervical lesions provides surgeons with an effective means of lesion location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…There are only four reported cases of lateral cervical adenectomy using US‐guided hookwire localization 37–39 . Park et al reported a series of eight cases of preoperative ultrasound‐guided hookwire needle localization of nonpalpable cervical mass 40 . To our knowledge, the impact of the use of the ultrasound‐guided hookwire on the operative time has not been evaluated in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only four reported cases of lateral cervical adenectomy using US‐guided hookwire localization 37–39 . Park et al reported a series of eight cases of preoperative ultrasound‐guided hookwire needle localization of nonpalpable cervical mass 40 . To our knowledge, the impact of the use of the ultrasound‐guided hookwire on the operative time has not been evaluated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasound or CT‐guided hookwire in cervical surgery was recently reviewed 27,28 and several studies reported its use in resection of benign or malignant lesions 11,29–42 . There are only four reported cases of lateral cervical adenectomy using US‐guided hookwire localization 37–39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of the breast surgery literature, the largest case series is by Park et al, reporting eight patients whose cervical masses were excised using HWL technique under US guidance, six of whom had previously neck surgeries. 1 Under CT guidance, there have been only two case reports describing the technique to aid the excision of a pelvic node in metastatic prostate cancer, and an inguinal node in recurrent rectal cancer. 2,3 HWL must be performed on day of surgery as the wire is external to the patient.…”
mentioning
confidence: 99%